A Prospective, Randomized Trial Testing Different Regimens of Carbohydrate Administration to Prevent Major Reduction in Plasma Glucose Follwing a Standardized Bout of Moderate Physical Activity in Patients with Type 1 Diabetes - Frenzke, Hanna; Varnhorn, Annette; Schulze, Heike; Kahle-Stephan, Melanie; Nauck, Michael A. (Experimental and Clinical Endocrinology & Diabetes, 2020)
Aim/Hypothesis It was the aim to prospectively study regimes of “preventive” carbohydrate administration to avoid major reduction in plasma glucose during physical activity.Methods 24 patients with type 1 diabetes (age 41±12 years; 11 women, 13 men; BMI 26.5±4.7 kg/m2; HbA1c 9.1±1.5%; insulin dose 0.64±0.22 IU/kg body weight and day) participated in one experiment without physical activity and in three experiments with a 4 km, 60 min hike starting at 2 p.m.. No “preventive” carbohydrates, 2×10 g or 2×20 g carbohydrates (muesli bars) were taken when starting and after 30 min (randomized order). Plasma glucose was determined.Results Within 30 min after starting physical activity, plasma glucose fell by approximately 70 mg/dl, making additional carbohydrate intake necessary in 70% of the subjects. This drop was not prevented by any regimens of “preventive” carbohydrate intake. After the nadir, plasma glucose rose faster after the 2×20 g carbohydrate regime (the largest amount tested; p=0.0036). With “preventive” administration of carbohydrates, significantly (p<0.05) less additional “therapeutic” carbohydrates needed to be administered in 6 h following the initiation of the hike.Conclusions/Interpretation In conclusion, in the setting of 2 h postprandial exercise in type 1 diabetes, preventive carbohydrate supplementation alone will not completely eliminate the risk of brisk falls in plasma glucose concentrations or hypoglycaemic episodes. Else, higher amounts or repeated administration of carbohydrates may be necessary.
Keywords: Insulin; hypoglycaemia; exercise; type 1 diabetes; physical activity; carbohydrate intake; muscle glucose uptake